Methane Transport during a Controlled Release in the Vadose Zone. Issue 1 (5th July 2018) - Felice, Mark; de Sieyes, Nick; Peng, Juan; Schmidt, Radomir; Buelow, Maya; Jourabchi, Parisa; Scow, Kate; Mackay, Douglas
Abstract : Core Ideas: Vadose zone CH4 migration was densely monitored during a controlled‐release scenario. Soil moisture strongly influenced vadose zone CH4 fate and CH4 oxidation. Soil CH4 fate appears primarily controlled by biological CH4 oxidation. Shallow, small‐rate releases of ethanol‐blended fuels from underground storage tanks (USTs) may be quite common and result in subsurface CH4 generation. However, vadose zone transport of CH4 generated from these fuel releases is poorly understood, despite the potential to promote vapor intrusion or create explosion hazards. In this study, we simulated shallow CH4 generation with a controlled subsurface CH4 release from July 2014 to February 2015 to characterize subsurface CH4 migration and surface emissions and to determine environmental controls on CH4 fate and transport. July 2014 through November 2014 was an extended period of drought followed by precipitation during December 2014. Throughout the experiment, under varied CH4 injection rates, CH4 formed a radially symmetrical plume around the injection point. Surface efflux during the drought period of the experiment was relatively high and stable, with approximately 10 to 11 and 34 to 52% of injected CH4 reaching the ground surface during the low‐ and high‐rate injections, respectively. Following the period of precipitation and increased soil moisture, efflux dropped and stabilized at approximately 1% of injected CH4, even as soil moisture began to decrease again. Tracer and inhibitor experiments and estimates of soil diffusivity suggest that microbial CH4 oxidation was responsible for the observed drop in efflux. The decrease in efflux only after soil moisture increased suggests a strong environmental control over the transport and oxidation of vadose zone CH4 .